Mobile broadband switching barriers in South Africa - Morony, Stephen James (My University, 2012)
This research was conducted to understand why consumers would not switch mobile broadband providers in a market place with increasing competition across all components of a telecommunications company, from international bandwidth to radio access network. This study makes use of in-depth interviews to investigate consumers’ views of switching barriers as they see them. The ability to obtain information in the consumers’ own words adds to the credibility of this research. The study makes use of the typology developed by Burnham as a framework for the analysis of switching barriers in mobile broadband. It is concluded that the typology is for the most part acceptable for classifying and understanding the barriers faced by consumers when attempting to switch providers. The key findings of this research are: consumers are cautious of switching service providers; they are hindered in doing so; the lack of differentiation by existing firms inhibits customers from switching; the current processes employed by firms further inhibit the potential for a customer to adopt their product.
MBA thesis - WBS
Keywords: Mobile broadband; Telecommunications